Human induced pluripotent stem cells technology in treatment resistant depression: novel strategies and opportunities to unravel ketamine's fast-acting antidepressant mechanisms. (October 2020) - Marcatili, Matteo; Sala, Carlo; Dakanalis, Antonios; Colmegna, Fabrizia; D'Agostino, Armando; Gambini, Orsola; Dell'Osso, Bernardo; Benatti, Beatrice; Conti, Luciano; Clerici, Massimo
Approximately 30% of Major Depressive Disorder (MDD) patients develop treatment-resistant depression (TRD). Among the different causes that make TRD so challenging in both clinical and research contexts, major roles are played by the inadequate understanding of MDD pathophysiology and the limitations of current pharmacological treatments. Nevertheless, the field of psychiatry is facing exciting times. Combined with recent advances in genome editing techniques, human induced pluripotent stem cell (hiPSC) technology is offering novel and unique opportunities in both disease modelling and drug discovery. This technology has allowed innovative disease-relevant patient-specific in vitro models to be set up for many psychiatric disorders. Such models hold great potential in enhancing our understanding of MDD pathophysiology and overcoming many of the well-known practical limitations inherent to animal and post-mortem models. Moreover, the field is approaching the advent of (es)ketamine, a glutamate N-methyl-d -aspartate (NMDA) receptor antagonist, claimed as one of the first and exemplary agents with rapid (in hours) antidepressant effects, even in TRD patients. Although ketamine seems poised to transform the treatment of depression, its exact mechanisms of action are still unclear but greatly demanded, as the resulting knowledge may provide a model to understand the mechanisms behind rapid-acting antidepressants, which may lead to the discovery of novel compounds for the treatment of depression. After reviewing insights into ketamine's mechanisms of action (derived from preclinical animal studies) and depicting the current state of the art of hiPSC technology below, we will consider the implementation of an hiPSC technology-based TRD model for the study of ketamine's fast acting antidepressant mechanisms of action.